Spesolimab Efficacy and Safety in Patients with Moderate-to-Severe Palmoplantar Pustulosis: A Multicentre, Double-Blind, Randomised, Placebo-Controlled, Phase IIb, Dose-Finding Study - A. David Burden; Robert Bissonnette; Alexander A. Navarini; Masamoto Murakami; Akimichi Morita; Thomas Haeufel; Binqi Ye; Frank Baehner; Tadashi Terui (Adis, Springer Healthcare, 2023)
Abstract Introduction We evaluated the anti-interleukin-36 receptor antibody spesolimab in patients with moderate-to-severe palmoplantar pustulosis (PPP). Methods This phase IIb trial comprised a loading dose period to week (W) 4, then maintenance dosing to W52. Patients were randomised 2:1:1:1:2 to subcutaneous spesolimab 3000 mg to W4 then 600 mg every 4 weeks (q4w), spesolimab 3000 mg to W4 then 300 mg q4w, spesolimab 1500 mg to W4 then 600 mg q4w, spesolimab 1500 mg to W4, 300 mg q4w to W16 then 300 mg every 8 weeks (q8w), or placebo switching to spesolimab 600 mg q4w at W16. The primary efficacy endpoint was percentage change from baseline in Palmoplantar Pustular Area and Severity Index (PPP ASI) at W16. Secondary endpoints included a Palmoplantar Pustular Physician's Global Assessment (PPP PGA) score of 0/1. Safety (including adverse events [AEs], local tolerability) was assessed. Results 152 patients were treated. The primary endpoint was not met; mean differences for spesolimab versus placebo ranged from − 14.6% (95% confidence interval [CI]: − 31.5%, 2.2%) to − 5.3% (95% CI: − 19.1%, 8.6%); none reached significance. At W16, 23 (21.1%) and two (4.7%) patients in the combined spesolimab and placebo groups, respectively, achieved PPP PGA 0/1 (mean difference 16.4%; 95% CI: 3.8%, 25.7%), increasing to 59 (54.1%; combined spesolimab) and 12 (27.9%; placebo switch to spesolimab) patients at W52. Non-Asian patients had significant improvements in the primary endpoint (mean difference − 17.7%; nominal P = 0.0394) and PPP PGA 0/1 at W16 with spesolimab versus placebo. Rates of AEs and AE-related discontinuations were similar for spesolimab and placebo. Local tolerability events and injection-site reactions were more frequent with spesolimab than placebo. Conclusion The primary objective to demonstrate a non-flat dose-response relationship and proof-of-concept was not achieved; improvements with spesolimab occurred in secondary endpoints and in non-Asian patients, indicating potential modest benefits. Spesolimab was generally well tolerated (ClinicalTrials.gov NCT04015518).